Calibration Data and Data from Andrill - Staudigel, Philip; Frank, T; Dunham, D; Fielding, C; Swart, P (IEDA: EarthChem Library, 2020)
Abstract: This dataset reports δ13C, δ18O, and Δ47 of carbonate phases recovered from a core in McMurdo Sound by ANtarctic geologic DRILLing (ANDRILL-2A). Other Description: Staudigel, P.T., Frank, T.D., Dunham, D.P., Fielding, C.R. and Swart, P.K. Cryogenic brine as a diagenetic fluid: reconstructing the cementation history of sediments in the Victoria Land Basin of Antarctica using clumped isotope geochemistry, Geochimica et Cosmochimica Acta,224, 154-170.